EMERGENCY SWRGICAL TREATMENT FOR BLEED!NG ESOPHAGEAL VARICES WHEN ENDOSCOP!C SCLEROTHERAPY FAlLS: A PROSPECTNE STUDY - Musa Akoğlu; Vedat KIRIMLIOĞLU; A. Remzi DALAY; Fatih HİLMİOĞLU; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-